1979
DOI: 10.1109/tmag.1979.1060271
|View full text |Cite
|
Sign up to set email alerts
|

MFTF test coil construction and performance

Abstract: A solenoid coil, 105 cm inside and 167 cm out side diameter, has been constructed and tested to study the performance of the stabilized Nb-Ti conductor to be used in the Mirror Fusion Test Facility (MFTF) being built at Lawrence Livermore Laboratory. The insulation system of the test coil is identical to that envisioned for MFTF. Cold-weld joints were made in the conductor at the start and finish of each layer; heaters were fitted to some of these joints and also to the conductor at various locations in the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The validity of this theoretical model has been verified experimentally. In particular, tests on a large experimental coil at the Lawrence Livermore Laboratory have demonstrated a similar growth from an artifically induced normal zone (5). It has also been shown that the normal zone propagates from coil to coil as well a?…”
Section: It Is Assumed Thatmentioning
confidence: 84%
“…The validity of this theoretical model has been verified experimentally. In particular, tests on a large experimental coil at the Lawrence Livermore Laboratory have demonstrated a similar growth from an artifically induced normal zone (5). It has also been shown that the normal zone propagates from coil to coil as well a?…”
Section: It Is Assumed Thatmentioning
confidence: 84%
“…where: B = field in tesla. (6) where the constant Cz and unknown exponents m, n may be evaluated by curve fitting the finite element predicted and measured velocity data for the various conductors.…”
Section: Simulation and Test Datamentioning
confidence: 99%